Mitochondrial function and antioxidative defence in human muscle: effects of endurance training and oxidative stress - Tonkonogi, Michail (Blackwell Science Inc, 2000)
1. The influence of endurance training on oxidative phosphorylation and the susceptibility of mitochondrial oxidative function to reactive oxygen species (ROS) was investigated in skeletal muscle of four men and four women. Mitochondria were isolated from muscle biopsies taken before and after 6 weeks of endurance training. Mitochondrial respiration was measured before and after exposure of mitochondria to exogenous ROS (H(2)O(2)+ FeCl(2)). 2. Endurance training increased peak pulmonary O(2) uptake (V̇(O(2),peak)) by 24 % and maximal ADP-stimulated mitochondrial oxygen consumption (state 3) by 40 % (P < 0.05). Respiration in the absence of ADP (state 4), the respiratory control ratio (RCR = state 3/state 4) and the ratio between added ADP and consumed oxygen (P/O) remained unchanged by the training programme. 3. Exposure to ROS reduced state 3 respiration but the effect was not significantly different between pre- and post-training samples. State 4 oxygen consumption increased after exposure to ROS both before (+189 %, P < 0.05) and after training (+243 %, P < 0.05) and the effect was significantly higher after training (P < 0.05, pre- vs. post-training). The augmented state 4 respiration could in part be attenuated by atractyloside, which indicates that ADP/ATP translocase was affected by ROS. The P/O ratio in ROS-treated mitochondria was significantly lower (P < 0.05) compared to control conditions, both before (−18.6 ± 2.2 %) and after training (−18.5 ± 1.1 %). 4. Muscle activities of superoxide dismutase (mitochondrial and cytosolic), glutathione peroxidase and muscle glutathione status were unaffected by training. There was a positive correlation between muscle superoxide dismutase activity and age (r= 0.75; P < 0.05; range of age 20–37 years), which may reflect an adaptation to increased generation of ROS in senescent muscle. The muscle glutathione pool was more reduced in subjects with high activity of glutathione peroxidase (r= 0.81; P < 0.05). 5. The influence of short-term training on mitochondrial oxygen consumption has for the first time been investigated in human skeletal muscle. The results showed that maximal mitochondrial oxidative power is increased after endurance training but that the efficiency of energy transfer (P/O ratio) remained unchanged. Antioxidative defence was unchanged after training when expressed relative to muscle weight. Although this corresponds to a reduced antioxidant protection per individual mitochondrion, the sensitivity of aerobic energy transfer to ROS was unchanged. However, the augmented ROS-induced non-coupled respiration after training indicates an increased susceptibility of mitochondrial membrane proton conductance to oxidative stress.